أهمية المراجعة والتحرير كخطوة أخيرة في عملية الترجمة - الشريف محمد عاشور (مجلة الاصالة, 2026)
Revision and editing are widely recognized as essential components of the translation process, yet they remain understudied and often undervalued in translation training and practice. This research paper investigates the importance of revision and editing as the final step in translation, with a focus on how these processes enhance accuracy, coherence, readability, professionalism, and overall quality. Drawing upon major translation studies theorists such as Mossop, Nord, House, and guidelines from ISO 17100, the paper outlines the theoretical foundations of revision and editing and explains their distinct functions. The study adopts a combined methodology consisting of theoretical analysis and a practical component involving the translation of a media text, followed by a detailed revision and editing procedure. The analysis demonstrates how revision corrects linguistic, semantic, and stylistic errors and ensures consistency, while editing improves clarity, readability, and naturalness in the target language. Findings reaffirm that revision and editing are indispensable stages that contribute significantly to quality assurance and professional translation standards. The paper concludes with recommendations for translators, educators, and institutions to integrate structured revision practices into their workflow and training programs.